2018
DOI: 10.1002/hed.25210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell‐phone radiofrequency on angiogenesis and cell invasion in human head and neck cancer cells

Abstract: Our investigation reveals that cell-phone radiofrequency could enhance head and neck cancer by stimulating angiogenesis and cell invasion via Erk1/Erk2 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…For instance, it can aid in understanding the mechanisms of cancer metastasis as well as the effect of certain inhibitors, drugs, or radiation on cancer metastasis using various cell types. In the earlier studies, using the chicken embryo CAM assay and in vitro cell culture, our group showed that cell-phone radio frequency can promote angiogenesis and cancer cell invasion [41]; additionally, the effect of cell-phone radio frequency on cancer cell metastasis can be verified using this model. Our ex ovo model also overcomes some of the limitations of widely-used zebrafish models [42].…”
Section: Discussionmentioning
confidence: 93%
“…For instance, it can aid in understanding the mechanisms of cancer metastasis as well as the effect of certain inhibitors, drugs, or radiation on cancer metastasis using various cell types. In the earlier studies, using the chicken embryo CAM assay and in vitro cell culture, our group showed that cell-phone radio frequency can promote angiogenesis and cancer cell invasion [41]; additionally, the effect of cell-phone radio frequency on cancer cell metastasis can be verified using this model. Our ex ovo model also overcomes some of the limitations of widely-used zebrafish models [42].…”
Section: Discussionmentioning
confidence: 93%